2022
DOI: 10.1002/ajh.26659
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus vaccine and VITT antibody induction

Abstract: We recently reported on a 25-year-old female without a history of heparin exposure, presenting with thrombocytopenia, thrombosis, and elevated D-dimer levels 10 days after nine-valent human papillomavirus (HPV) vaccination (Gardasil, Merck and Co). 1 The patient's samples activated platelet factor 4 (PF4)-treated platelets and recognized PF4-polyanion complexes in heparin-induced thrombocytopenia (HIT) ELISA (PF4-polyanion enzyme-linked immunosorbent assay).As previously noted, 1 thrombosis sites included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Consistent with VITT, the patient presented with thrombocytopenia and thrombosis, had elevated D-dimer levels, strong positivity in HIT ELISA, and tested positive for platelet-activating anti-PF4 antibodies in the PEA(66). This sample was tested in the un-complexed PF4 ELISA, yielding strong positivity in that assay, also consistent with VITT([ 67 ]). This case is especially noteworthy as it should raise clinician awareness of the possibility of VITT even after non-covid-19 vaccines.…”
Section: Vitt After Non-adenoviral Vector-based Vaccinesmentioning
confidence: 79%
“…Consistent with VITT, the patient presented with thrombocytopenia and thrombosis, had elevated D-dimer levels, strong positivity in HIT ELISA, and tested positive for platelet-activating anti-PF4 antibodies in the PEA(66). This sample was tested in the un-complexed PF4 ELISA, yielding strong positivity in that assay, also consistent with VITT([ 67 ]). This case is especially noteworthy as it should raise clinician awareness of the possibility of VITT even after non-covid-19 vaccines.…”
Section: Vitt After Non-adenoviral Vector-based Vaccinesmentioning
confidence: 79%
“…However, which constituent(s) in the vaccines might cause(s) conformational changes in PF4 through electrostatic interactions to trigger the immune response [46][47][48] is unresolved. The observation of a VITT-like syndrome after human-papilloma virus (HPV) 49 vaccination suggests a range of factors may trigger conformational changes in PF4, similar to the HIT antigen that can be induced by diverse polyanions 50 . Figure 1, Panel A summarizes some of the current hypotheses on the generation of VITT antibodies.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Kanack et al have reported an un-complexed PF4 ELISA which sensitively and specifically detects anti-PF4 VITT antibodies and can differentiate spontaneous HIT from VITT (150). Additionally, they found that the quantification of thrombospondin-1 (TSP1) released from PF4/heparin-treated cryopreserved platelets is accurate for detecting and potentially differentiating VITT and HIT patient antibodies (151).…”
Section: Measuring Platelet-activating Anti-pf4 Igg Is Critical For D...mentioning
confidence: 99%